Pengaruh Persepsi Kebermanfaatan dan Kemudahan Bagi Pengusaha Kena Pajak Terhadap Minat Menggunakan e-Faktur di Empat KPP Pratama Bandung Raya - Fitri Puspitasari; Riauli Susilawaty Hutapea; Yeti Apriliawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
E-Facture is implemented to overcome the problem of the tax revenue system because fictitious invoices such as criminal cases against the application of tax have become a very controversial discussion in Indonesia, the discovery of evidence of tax levies that are very detrimental to the state and the business world. The system of e-Facture raises various polemics, especially obstacles in its application. This study aims to determine the effect of perceived usefulness and perceived ease of use for taxable entrepreneur. This study uses a descriptive method with a quantitative approach. The population is a Taxable Entrepreneur Entity with a total sample of 60 respondents. The data analysis technique used multiple linear regression analysis with the IBM SPSS Version 25 program. The results showed that perceived usefulness and perceived ease of use had a positive and significant effect on behaviour intention to use e-Facture.